2008
DOI: 10.1103/physreve.78.021301
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength and force transmission in granular media with rolling resistance

Abstract: We investigate a class of granular materials characterized by the possibility of interlocking between the particles. The interlocking is modeled by its effect through rolling resistance depending on relative rotation and normal force at the contact points and involving a single parameter analogous to the sliding friction coefficient. The model, which is introduced in the framework of the contact dynamics method, is applied to simulate the simple shear of a large granular sample. We present a detailed analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 24 publications
12
98
0
6
Order By: Relevance
“…In CD, an iterative algorithm based on nonlinear Gauss-Seidel iterations is used to determine the contact forces and particle velocities simultaneously at all potential contacts. The CD method has been extensively employed for the simulation of granular materials in 2D and 3D [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Bonded Cell Modelmentioning
confidence: 99%
“…In CD, an iterative algorithm based on nonlinear Gauss-Seidel iterations is used to determine the contact forces and particle velocities simultaneously at all potential contacts. The CD method has been extensively employed for the simulation of granular materials in 2D and 3D [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Bonded Cell Modelmentioning
confidence: 99%
“…The distributions are similar with nearly the same privileged direction aligned with the principal stress direction θ σ but with increasing anisotropy as a function of ξ. They all can be approximated by their truncated Fourier expansion [11,13,15]:…”
Section: A Granular Texturementioning
confidence: 99%
“…For example, it is found that in highly polydisperse systems the force chains are mainly captured by large particles so that the shear strength of a noncohesive granular material is practically independent of particle size distribution [12]. As another important example, a parametric study shows that when the particles interact by both sliding friction and high rolling resistance at their contacts, the nature of the weak network is affected by the formation of columnar structures which do not need to be propped by a particular class of weak contacts [13].…”
Section: Introductionmentioning
confidence: 99%
“…In granular systems under loading, the force chains engaged along the entire system are a clear evidence of long-range interactions [18]. These chains connect the microscopic contact forces with the global resistance to external forces, as shear for example [19]. Thus, it is natural to associate the emergence of these force chains at mesoscopic scales with the departure from the classical Boltzmann-Gibbs (BG) statistics in these systems.…”
mentioning
confidence: 99%